2011
DOI: 10.1111/j.1745-4514.2011.00564.x
|View full text |Cite
|
Sign up to set email alerts
|

STUDIES ON ANTIOXIDANT PROPERTIES OF THE DIFFERENT SOLVENT EXTRACTS AND FATTY ACID COMPOSITION OFHYOSCYAMUS RETICULATUSL.

Abstract: Hyoscyamus reticulatus (Solanaceae) is distributed in the Mediterranean, East and Central Anatolia regions of Turkey. In the present study, antioxidant properties of the various extracts of H. reticulatus were evaluated by seven different chemical assays, namely total phenolics and flavonoids content, total antioxidant capacity, free radical (2,2‐diphenyl‐1‐picrylhydrazyl)‐scavenging assay, β‐carotene/linoleic acid test system, and ferric‐ and cupric ion‐reducing power. The strongest antioxidant properties wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
(70 reference statements)
0
7
0
1
Order By: Relevance
“…For instance, squalene is identified as one of the major compounds in AMF and reported to possess antioxidant (Kohno et al 1995) and chemopreventive activities (Newmark 1997;Musakeshavarz & Abdul-Reza 2012). Among other identified components, dodecanoic acid (Guler 2012) is reported to have antioxidant and antimicrobial activities. Tetradecanoic acid and hexadecanoic acid are reported to be antioxidant, anti-inflammatory and cancer preventive effects (Bodoprost and Rosemeyer 2007).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, squalene is identified as one of the major compounds in AMF and reported to possess antioxidant (Kohno et al 1995) and chemopreventive activities (Newmark 1997;Musakeshavarz & Abdul-Reza 2012). Among other identified components, dodecanoic acid (Guler 2012) is reported to have antioxidant and antimicrobial activities. Tetradecanoic acid and hexadecanoic acid are reported to be antioxidant, anti-inflammatory and cancer preventive effects (Bodoprost and Rosemeyer 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acid compositions of the extract are shown in Table S10. All the detected fatty acids in T65 crude product have been reported to have antioxidant activity [62][63][64][65][66].…”
Section: Fatty Acidsmentioning
confidence: 96%
“…Since it has pharmacologically active substances, it has attracted the attention of researchers, and antioxidant and antimicrobial studies of this species have been reported. When the ethanolic extract of H. reticulatus leaves was analyzed, total phenolic content was found to be 130.06 mg/g and total flavonoid content was 243.7 mg/g [3]. Although there are no data on material losses due to poisoning caused by poisonous plants in Turkey, it is reported that approximately 3%-5% of animals are poisoned with plants every year in countries where pasture improvement is done, such as the United States [4].…”
Section: Introductionmentioning
confidence: 99%
“…The poisoning of two people who ate fresh shoots of Hyoscyamus niger because of its similarity to lettuce is an example, and henbane poisoning is common in Eastern Anatolia [5,6,7]. Consumption of the fresh shoots, roots, and seeds of H. niger can cause hallucinations, blurred vision, increased heart rhythm, and death [2,3,8,9]. Similarly, a 71-year-old patient with a diagnosis of bronchial asthma drank tea made from the leaves of many henbane plants because he had heard it was good for asthma, and approximately two hours later, he was hospitalized with symptoms including visual and speech disorders, dry mouth, and palpitations [10].…”
Section: Introductionmentioning
confidence: 99%